Pharmacokinetic Properties of Clarithromycin: A Comparison with Erythromycin and Azithromycin - Marc LeBel (Canadian Journal of Infectious Diseases, 1993)
Objective: To compare the pharmacokinetic properties of two new macrolide antibiotics, clarithromycin and azithromycin, with those of the prototype macrolide, erythromycin.